Bacteriological Profile of Suspected Neonatal Septicaemia and Its Relationship with Selected Risk Factors (Medicine Today, 2022)
Introduction: Neonatal septicaemia is one of the major problem in neonatology with a high case fatality rate. Manifestations of neonatal septicaemia are subtle & non-specific. Blood culture is the “gold standard” in the diagnosis of neonatal septicaemia, a high index of suspicion with or without laboratory evidences of infection is the key for early diagnosis. Early diagnosis & introduction of antibiotic may reduce mortality and morbidity.Objective: To explore the bacterial organisms among the suspected neonatal septicaemic cases and its relationship with selected risk factors.Materials and Methods: A Cross sectional descriptive type of study was carried out on all suspected cases of neonatal septicaemia patients admitted in the paediatric wards of Rajshahi Medical College Hospital during the period of july 2008 to june 2010 .Total 60 sixty cases who had non- specific symptoms of septicaemia were enrolled in this study. After a clinical evaluation and management of the patient blood culture was performed on all neonates with risk factors or signs suggestive of sepsis.Results: Out of sixty cases of suspected neonatal septiceamic newborns 18.33% were culture positive for bacteria. Both gram negative and gram positive bacteria were responsible for neonatal septicaemia. Majority of the organisms were gram negative (54.5%) and most common organisms was E.coli (54.5%) .Other gram-positive organisms were streptococcus spp(27.3%) and staph aureus(18.2%) respectively. Among blood culture positive cases 82% were early onset neonatal septicaemia & 18% were late onset septisaemia. Gestational age, Low birth weight, Low socioeconomic status of mother, mode of delivery and birth asphyxia were risk factor for both early onset neonatal sepsis & late onset neonatal sepsis.Conclusion: Septicaemia is one of the major causes of death & its manifestations are subtle and non specific. Both gram negative & gram positive bacteria are responsible for neonatal septicaemia. Most isolated bacteria E.coli. Risk factors may be the factor for NNS. Although blood culture is the “gold standard” in the diagnosis of NNS, a high index of suspicion with or without laboratory evidences of infection is the key for early diagnosis. If we can avoid risk factors for NNS by antenatal check up of pregnant mother and thereby number of septicaemia could be reduced.Medicine Today 2022 Vol.34(1): 17-21